Nalar Epistemologi Kamaruddin Amin dalam Konstruksi Metode Kritik Sanad Hadis - Zahrah, Ummuz; Ridlo, Muhammad Abdurrasyid (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
This study aims to examine the methodology of hadith sanad criticism according to Kamaruddin Amin which can provide an answer to the question of the authenticity of Prophetic traditions based on historical studies. This study is a qualitative research based on literature review with descriptive and content analysis methods. The study presents Kamaruddin Amin's study in analyzing the hadith of fasting by elaborating the methods of hadith sanad criticism of Muslim and Western scholars. The conclusion of this study is to show that the results of the methods of Muslim scholars, Juynboll, and the one applied by Kamaruddin Amin in examining the hadith of fasting are historically different. The point that distinguishes it from the other two methods is the equal placement of the sanad and matan in determining the origin of a hadith. The recommendation for future researchers is to apply Kamaruddin Amin's method in reading the authenticity of other traditions.